Healthcare resource utilization and work loss in dermatomyositis and polymyositis patients in a privately-insured US population. (2nd July 2016) - Bradford Rice, J.; White, Alan; Lopez, Andrea; Galebach, Philip; Schepman, Patricia; Popelar, Breanna; Philbin, Michael
Abstract: Background Dermatomyositis and polymyositis (DM/PM) are inflammatory myopathies characterized by muscle inflammation/weakness. Patients with DM/PM have a reduced quality-of-life and are at an increased risk for several comorbidities. Studies have assessed the incidence and prevalence of DM/PM; however, no study has estimated the burden of the diseases in terms of both healthcare resource utilization (HCRU) and work loss incurred by patients. Objective To provide a comprehensive, current estimate of the annual HCRU and work loss in DM/PM patients in the US. Methods All patients (aged 18–64 years) with a first diagnosis of DM/PM between January 1, 1998 and March 31, 2014 ('index date') were selected from a de-identified privately-insured administrative claims database. DM/PM patients were required to have continuous health-plan enrollment 12 months prior to and following their index date. Propensity-score (1:1) matching of DM/PM patients with non-DM/PM controls was carried out based on a logistic regression of demographic characteristics, comorbidities, costs, and HCRU to control for these confounding factors. Burden of HCRU and work loss (disability days and medically-related absenteeism) were compared between the matched DM/PM and the non-DM/PM cohorts over the 12-month period after the index date ('outcome period'). Results Of the 2617 DM/PM patients that met sample selection criteria, 2587 (98.9%) were matched with a non-DM/PM control. During the outcome period, DM/PM patients had significantly increased HCRU across places of service, including 44% more inpatient admissions (3.6 vs 2.5, p < 0.001), increased visits with specialists such as rheumatologists, neurologists and physical therapists, and filled 4.7 more prescriptions (32.2 vs 27.5, p < 0.001) than matched control patients. The increased HCRU led to significantly more medically-related work loss among DM/PM patients than matched controls ( p < 0.001). Conclusions DM/PM imposes a substantial increase in healthcare resource use and is associated with statistically significantly greater work loss in the first year following diagnosis.